Efeito da oxigenoterapia hiperbárica em ratos submetidos à esplenectomia subtotal com preservação do polo inferior - Marcela Souza Lima Paulo (2010)
Purpose: Assess the effect of the hyperbaric oxygen therapy in ratssubmitted to total splenectomy as for the following aspects: survival rate and weight of the animals, feasibility and growing of the lower pole. Methods: Forty male Wistar rats, weighing between 274 g e 313g (MA 294,15g ± 10,33g), underwent total splenectomy preserving the lower pole and divided into two groups: group A (n=20) animals not treated with (nt) with hyperbaric oxygen; group B (n=20) - rats treated with hyperbaric oxygen. Groups A and B were subdivided into two groups of 10 animals each, according to the time the euthanasia took place: subgroup 15 days, subgroup 45 days. At the beginning of the experiment, the length, width and thickness of the lower pole of the spleen were measured. At the end of the experiment (15th and 45th days) the lower pole was once again measured, weighed and sent to morphological studies. Result: All the animals survived. There has been an increase in the weight of the animals of all subgroups from the beginning to the end of the experiment. However, there has been a decrease in the weight of the animals from the subgroup Bt15 and Bt45 within the period of ten days corresponding to the treatment with hyperbaric oxygen . The feasibility of the lower pole was more evident in the treated animals rather than in the animals not treated with hyperbaric oxygen on the 15th day, however it did not differ on the 45th day. The length, width and thickness of the lower pole remained unchanged on the 15th day in neither of the groups. On the 45th day of the postoperative period, there has been a growth in the lower pole (p<0,01) in the non-treated, and there has been a growth in the thickness of the mentioned pole (p<0,05) in the treated animals. The histological analysis showed a more intense cell proliferation in the groups A and B compared to the upper control-part of the spleen. The vascular and cellular increase in the animals treated with hyperbaric oxygen therapy was greater than in the non-treated animals. Conclusion: The hyperbaric oxygen therapy is responsible for the weightloss, but it does not affect the survival rate of the animals. It improves thefeasibility of the lower pole of the spleen, in spite of not interfering in its growth.